Outdoor performance analysis of different PV technologies under hot semi-arid climate. (November 2020) - Nour-eddine, Id omar; Lahcen, Boukhattem; Fahd, Oudrhiri Hassani; Amin, Bennouna; Aziz, Oukennou
Abstract: The outdoor performance evaluation of a 5.94 kWp grid connected photovoltaic (PV) system, implemented on the rooftop of the National School of Applied Sciences of Safi (NSASS) Morocco, has been carried out under hot semi-arid climate. The PV plant contains three silicon-based PV panels: mono-crystalline (m-Si), poly-crystalline (p-Si) and amorphous (a-Si). A one-year measured data from June 2018 to May 2019 were analyzed. The performance parameters such as reference yield, final yield, system efficiency, performance ratio, capacity factor, energy density and environmental benefits were assessed under IEC 61724 standards. Performance parameters results show that m-Si technology is the most suitable one for this location followed by p-Si. Knowing that m-Si's price is relatively higher than that of p-Si, the latter can further be considered as the most appropriate technology to the hot semi-arid climate of Safi region. Thereafter, the amount of CO2 emissions that could be avoided can reach 9.69 tons per year. Outcomes also indicate that grid connected PV plants are feasible in the hot semi-arid climate of Safi region for electricity generation and may contribute to the future energy mix of the country.